2009
DOI: 10.1186/1756-9966-28-28
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt activity induces the mesenchymal-to-epithelial reverting transition with restoring E-cadherin expression in KB and KOSCC-25B oral squamous cell carcinoma cells

Abstract: Background: The Akt/PKB family of kinases is frequently activated in human cancers, including oral squamous cell carcinoma (OSCC). Akt-induced epithelial-to-mesenchymal transition (EMT) involves downregulation of E-cadherin, which appears to result from upregulation of the transcription repressor Snail. Recently, it was proposed that carcinoma cells, especially in metastatic sites, could acquire the mesenchymal-to-epithelial reverting transition (MErT) in order to adapt the microenvironments and re-expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 37 publications
6
124
1
2
Order By: Relevance
“…In OSCC, Akt signaling has an important role in its progression, 41,42 and inhibition of Akt signaling suppresses malignant phenotype. 43 Recently, growing evidence has indicated a relationship between Notch signaling and tumor cell invasion. 44,45 Our present data demonstrated that the Notch1 expression influences the TNF-a-dependent invasiveness of OSCC cells via the transcriptional regulation of Slug and Twist, important regulators of cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In OSCC, Akt signaling has an important role in its progression, 41,42 and inhibition of Akt signaling suppresses malignant phenotype. 43 Recently, growing evidence has indicated a relationship between Notch signaling and tumor cell invasion. 44,45 Our present data demonstrated that the Notch1 expression influences the TNF-a-dependent invasiveness of OSCC cells via the transcriptional regulation of Slug and Twist, important regulators of cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, downregulation of ZEB1, Slug, Snail, SMA, or Twist is usually induced during MET (49,61,64). It was also found that progesterone (P4) can regulate the expression of Snail and other EMT-relevant proteins in the human breast cancer cell line MB468 and induce cell morphological reversion from mesenchymal to epithelial phenotypes via membrane progesterone receptor a (mPRa; ref.…”
Section: Transcriptional Factorsmentioning
confidence: 99%
“…43) or by progesterone (P4) in basal phenotype breast cancer (63) was related to the activity of Akt signaling. Intriguingly, inhibition of Akt activity by PIA (Akt inhibitor, phosphatidylinositol ether lipid analogs) decreased NF-kB signaling and led to downregulation of Snail and Twist expression (64). PIA treatment induced the expression of E-cadherin and b-catenin; downregulated vimentin; restored the epithelial morphology of a polygonal shape; and reduced tumor cell migration in KB and KOSCC-25B cells (64).…”
Section: Mechanism Of Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidylinositol 3-kinase (PI3K)/Akt/mTOR signaling has also been shown to be a target for the inhibition of EMT processes [15]. Akt inhibitors, such as phosphatidylinositol ether lipid analogs, have been shown to promote MET in squamous cell carcinomas of the oral cavity [24]. Rapamycin has also been proposed to hinder EMT based on its inhibitory effects on mTOR [15].…”
Section: Epithelial-to-mesenchymal Transition: Explanations For Tumormentioning
confidence: 99%